An accountability framework for technological innovation - Whitty, B. (2010)
Technological innovation in agricultural science forms an important element in the effort to reduce poverty. In this Brief, we offer recommendations to help an organization conducting technological research and design (R&D) to become more accountable. These recommendations are based on four principles developed by the One World Trust which capture the dimensions of accountability.